2014
DOI: 10.1016/j.chiabu.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple perpetrator rape among girls evaluated at a hospital-based Child Advocacy Center: Seven years of reviewed cases

Abstract: The aim of this study was to describe contextual events, abuse experiences, and disclosure processes of adolescents who presented to a hospital-based Child Advocacy Center for medical evaluation and evidentiary collection as indicated after experiencing multiple perpetrator rape during a single event (n = 32) and to compare these findings to a group of single perpetrator sexual assaults (n = 534). This study used a retrospective mixed-methods design with in-depth, forensic interviews and complete physical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
(43 reference statements)
2
16
0
Order By: Relevance
“…As in other studies ( Adams et al, 2007 ; Edinburgh, Saewyc, Thao, & Levitt, 2006 ) most sexually exploited girls in this study did not have gynecologic findings of penetrating trauma even though they had experienced this severe form of child abuse. One in 5 did, however, have transections of their hymen, which is similar to rates found among victims of gang rape ( Edinburgh, Pape-Blabolil, Harpin, & Saewyc, 2014 ). A high rate of sexually transmitted infection was also identified during health evaluations of sexually exploited youth.…”
Section: Discussionsupporting
confidence: 71%
“…As in other studies ( Adams et al, 2007 ; Edinburgh, Saewyc, Thao, & Levitt, 2006 ) most sexually exploited girls in this study did not have gynecologic findings of penetrating trauma even though they had experienced this severe form of child abuse. One in 5 did, however, have transections of their hymen, which is similar to rates found among victims of gang rape ( Edinburgh, Pape-Blabolil, Harpin, & Saewyc, 2014 ). A high rate of sexually transmitted infection was also identified during health evaluations of sexually exploited youth.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, any sexual exposure is considered to carry a risk when a condom is not used or is broken. The risk of HIV acquisition increases exponentially in the presence of factors such as genital trauma, genital ulcers, sexually transmitted infections (STIs), high viral load, blood exposure, ejaculation and rape by multiple assailants . In cases where the victim of an SA had known the assailant for > 24 h, it was found that the perception of risk was lower and the victim tended to consider the use of PEP unnecessary .…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to shed light on attribution of victim and perpetrator blame in rape cases and investigate whether and how these attributions are affected by the number of perpetrators (Experiment 1), and the level of force used by the perpetrators (Experiment 2). Most rapes occur in the victim’s own home, the perpetrator’s home, or at social gatherings they have attended with people they thought they could trust (e.g., Edinburgh, Pape-Blabolil, Harpin, & Saewyc, 2014; Lovett & Horvath, 2013), and we will, therefore, investigate attribution of blame in a home party setting. Although attributions of blame in MPR cases have not previously been experimentally investigated, there are reasons to believe that victim-blaming behavior and attitudes might be influenced by the number of perpetrators committing the crime.…”
mentioning
confidence: 99%